EXPERIENCE OF USING TB-TEST TECHNOLOGY (BIOCHIP-IMB, RUSSIA) WITHIN THE DIAGNOSTIC PROCEDURE - D. V. Vakhrusheva; N. I. Eremeeva; T. V. Umpeleva; K. V. Belousova (Туберкулез и болезни лёгких)
The article analyzes the results of using TB-Test technology (Biochip-IMB, Russia) within the diagnostic procedure for testing clinical specimens with the purpose of tuberculosis diagnostics and drug susceptibility testing in Ural Research Institute of Phthisiopulmonology. The use of this test system is feasible if there are at least 102 cells of tuberculous mycobacteria in 1 ml of the specimen, and there is a high level of multiple drug resistance in the region; and within 2-4 days one test allows detecting mutations associated with resistance to main first and second line TB drugs and performing intraspecific typing of mycobacteria, which is needed for epidemiological monitoring and detection of cases with nosocomial superinfection.